PENGEMBANGAN MEDIA AUGMENTED REALITY BERBASIS ETNOMATEMATIKA UNTUK PEMBELAJARAN KUBUS DAN BALOK DI SEKOLAH DASAR - Al Adawiyah, Wiya; Eka Sastrawati; Violita Zahyuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mathematics learning in elementary schools still faces challenges due to the abstract nature of the material and students’ low level of engagement. This study aimed to develop an ethnomathematics-based Augmented Reality (AR) learning medium centered on Muaro Jambi Temple for teaching cubes and rectangular prisms to sixth-grade elementary students, as well as to describe its levels of validity and practicality. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The product was developed using the Assemblr Edu platform by integrating 3D visualizations of three-dimensional geometric objects with the cultural context of Muaro Jambi Temple. The research subjects included content experts, media experts, language experts, teachers, and students. Data were collected through interviews and questionnaires. The results indicated that the ethnomathematics-based AR learning media were categorized as valid and practical for use in sixth-grade mathematics instruction. Therefore, this media is feasible to be used as an alternative contextual learning resource that supports the Merdeka Curriculum.